ANALISIS EKONOMI OBYEK WISATA EKOSISTEM MANGROVE DI KELURAHAN BERBAS PANTAI, KOTA BONTANG - Nurul Ovie Oktawati; Ardiansyah Ardiansyah (Jurnal Harpodon Borneo, 2018)
Bontang regency’s area is an area which have a significant contribution for underpinning people’s livelihood. There is a mangrove ecosystem are inside such area, it is profoundly benefitting for people around there, tourism for example.The aim of this research is to analyze economic valueof mangrove ecosystem tourism object in Brebas Sub-District in the beach area of Kota Bontang. Accidental sampling method, which is sample is defined accidentally is a employed in this research. The estimation of economic value of mangrove ecosystem tourism area is analyzed using Travel Cost Method (TCM)Its economic value is Rp. 16.213.329 per acre per year. This value is to be obtained based on visitation number and customer’s value surplus. Keyword : Economic values, tourism, mangrove ecosystem